Renal venotomy for thrombectomy and kidney preservation in dogs with adrenal tumors and renal vein invasion. Issue 4 (22nd February 2021) - Chiti, Lavinia E.; Mayhew, Philipp D.; Massari, Federico
Abstract: Objective: To describe the surgical technique and report the outcomes of adrenalectomy and thrombus removal with kidney preservation by renal venotomy in a population of dogs with adrenal tumors and vascular invasion into the renal vein (RV) and caudal vena cava (CVC). Study design: Short case series. Animals: Five client‐owned dogs that underwent adrenalectomy. Methods: Dogs with adrenal tumors and vascular invasion into the RV and CVC were retrospectively enrolled in this multi‐institutional study. Renal venotomy was performed at the time of adrenalectomy for tumor thrombus removal. Recorded data included signalment, clinical signs and results of laboratory testing, physical examination findings, diagnostic imaging results, surgical technique, surgical time, surgical complications, and outcome. Results: Tumor thrombus was removed by renal venotomy in five dogs. In one dog with an ectopic adrenal tumor located ventral to the left kidney, the thrombus was occluding 90% of caval flow, and a small caval venotomy was required to remove it. Kidney preservation was achieved in all dogs. No significant intraoperative or postoperative complications occurred, and all dogs were discharged 3 to 4 days postoperatively. Median surgical time was 125 minutes (range, 80‐210). At the end of the study, four dogs were alive without signs of recurrence, while one dog died of a suspected pulmonary embolism at 510 days. Median follow‐up was 510 days (range, 279‐890). Conclusion: Renal venotomy is feasible for thrombectomy in dogs with adrenal tumors and RV invasion and allowed for the preservation of the kidney in this case series, thus limiting perioperative morbidity.